The Organ Trail: A Review of Biomarkers of Organ Failure - Dao, Long; Ragoonanan, Dristhi; Yi, Sofia; Swinford, Rita; Petropoulos, Demetrios; Mahadeo, Kris M.; Li, Shulin (Frontiers in Oncology, 2020)
Pediatric organ failure and transplant populations face significant risks of morbidity and mortality. The risk of organ failure itself, may be disproportionately higher among pediatric oncology patients, as cancer may originate within and/or metastasize to organs and adversely affect their function. Additionally, cancer directed therapies are frequently toxic to organs and may contribute to failure. Recent reports suggest that nearly half of providers find it difficult to provide prognostic information regarding organ failure due to unknown disease trajectories. Unfortunately, there is a lack of uniform methodology in detecting the early symptoms of organ failure, which may delay diagnosis, initiation of treatment and hinder prognostic planning. There remains a wide array of outstanding scientific questions regarding organ failure in pediatrics but emerging data may change the landscape of prognostication. Liquid biopsy, in which disease biomarkers are detected in bodily fluids, offers a noninvasive alternative to tissue biopsy and may improve prompt detection of organ failure and prognostication. Here, we review potential liquid biopsy biomarkers for organ failure, which may be particularly useful among pediatric oncology patients. We synthesized information from publications obtained on PubMed, Google Scholar, clinicaltrials.gov, and Web of Science and categorized our findings based on the type of biomarker used to detect organ failure. We highlight the advantages and disadvantages specific to each type of organ failure biomarker. While much work needs to be done to advance this field and validate its applicability to pediatric cancer patients facing critical care complications, herein, we highlight promising areas for future discovery.